2016
DOI: 10.3390/nu8100592
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Epidemiology of Serum 25-Hydroxyvitamin D Concentrations among Healthy Adults Living in Rural and Urban Areas in Mongolia

Abstract: Many factors put Mongolians at risk of vitamin D deficiency. Despite low levels observed in Mongolian children and pregnant women, there are few data published on the vitamin D status of non-pregnant adults. Between summer 2011 and winter 2013, paired summer and winter blood samples were collected from 320 healthy men and women (20–58 years) living in eight Mongolian provinces. Mean serum 25(OH)D concentrations were 22.5 ng/mL (95% CI: 14.5, 32.5) in summer and 7.7 ng/mL (95% CI: 4.6, 10.8) in winter, with a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 19 publications
2
24
1
Order By: Relevance
“…Prior research by our group and others has demonstrated extremely low levels of consumption and biochemical status of vitamin D among Mongolians of different ages across the country, a high prevalence of rickets nationwide, and that vitamin D fortification of milk consumed by school children was effective in ameliorating biochemical vitamin D deficiency [ 4 , 5 , 16 ]. We have also observed beneficial effects of vitamin D supplementation on child growth, risk of respiratory infections, and risk of atopic dermatitis in Mongolia [ 41 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research by our group and others has demonstrated extremely low levels of consumption and biochemical status of vitamin D among Mongolians of different ages across the country, a high prevalence of rickets nationwide, and that vitamin D fortification of milk consumed by school children was effective in ameliorating biochemical vitamin D deficiency [ 4 , 5 , 16 ]. We have also observed beneficial effects of vitamin D supplementation on child growth, risk of respiratory infections, and risk of atopic dermatitis in Mongolia [ 41 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although wheat flour has become much more important in recent centuries, the modern Mongolian diet still consists largely of dairy products and red meat, and little fruits, non-tuberous vegetables, legumes, nuts and seeds, and seafood [ 2 , 3 ]. Despite steady and impressive progress in curbing wasting, stunting, and low birth weight, a persisting lack of diversity in the Mongolian diet underlies a high prevalence of multiple biochemical micronutrient deficiencies among women and children, including those of iron, vitamin A, and vitamin D [ 4 , 5 ]. Micronutrient deficiencies in women of reproductive age pose a threat to their health, as well as the health of their offspring during pregnancy and nursing, and may lead to severe and permanent physical and cognitive deficits [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As fasting is not required for accurate measurement of the biomarkers of interest, serum was collected at random times during the day in order to avoid systematic error in dietary measurements that could occur from interrupting all subjects at the same time (e.g., before breakfast). Details of the dietary assessment, blood collection, and anthropometry have been described earlier [9,17].…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
“…While childhood stunting and vitamin A deficiency have decreased over the past two decades, this period has also seen a sharp rise in the prevalence of adolescent and adult overweight and type 2 diabetes [7,8]. Currently, almost one third of pregnant women are anemic, less than two thirds of infants are reportedly exclusively breastfed up to six months of age, and vitamin D deficiency is endemic [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…In spring, summer and autumn season, the urbanization degree differences on vitamin D status was concerned [11,26]. These differences mainly be attributed to the particularities of the physical environment which could be more supportive of increased outdoor physical activity levels and consequently greater sun exposure in rural area [27].…”
Section: Discussionmentioning
confidence: 99%